Variáveis relacionadas ao comportamento da mulher vítima de violência doméstica avaliadas pela escala ASR no aspecto de manter ou não o vínculo com o parceiro autor da violência - Souza, Josane Bairros de (2017)
The relevant problem related to violence against women we have a relatively persistent phenomenon regarding the return of a large percentage of women to their aggressor. This study proposes to evaluate the behavioral difference between women victims of domestic violence in the facet of maintaining or not the relationship with aggressive partners . The survey was conducted in the city of Porto Alegre Metropolitan Region, Canoas / RS, with 152 women victims of violence through the collection of data by the ASR (Adult Self Report) scale that evaluates: syndromes, adaptive functioning, substance use , Severe psychopathologies guided by the Diagnostic and Statistical Manual of Mental Disorders (DSM). The women also answered the socio-demographic questionnaire, prepared for the research. This study showed 40% return of women to their abusers. We did not observe association with ASR global score nor with the 4 subscales. We found association only in 10 of the 19 items analyzed, such as: Good relationship with the family of origin (RR 1.76); Adaptive Medium - Adaptation Capabilities (RR 2.17); Personal Skills - Adaptation (RR 1.75); Anxiety / Depression (RR 1.49); Aggressive Behavior (RR 1.61); Internalizing Problems (RR 1.67); Depression (RR 1.47); Avoidant Personality Disorder (RR 1.56); Antisocial Personality (RR 1.74). In relation to the sociodemographic questionnaire, the results showed protection factors for nonreconciliation of the relationship with the aggressor between the groups were: having a formal and formal work with a formal contract and fomenting through a government grant. Our data suggest that to a large extent, the women in our sample do not have severe psychopathological characteristics that may be considered as determining factors for maintaining the relationship with the aggressor partner. Only those related to character or perception of their adaptive abilities. Environmental, family, legal, police and social support is essential for these women to break the cycle of violence in their marital relationship and to seek new life goals with autonomy and security in the development of their potentialities.